2016
DOI: 10.1177/0284185116628339
|View full text |Cite
|
Sign up to set email alerts
|

Which system is better to predict prognosis of patients with hepatocellular carcinoma treated by transcatheter arterial chemoembolization as initial therapy? Comparison between CLIP and JIS in a Japanese population

Abstract: Background There has been no consensus as to which system, either the Cancer of the Liver Italian Program (CLIP) or the Japan Integrated Staging (JIS) system, is suitable to predict the prognosis of hepatocellular carcinoma (HCC) patients who underwent transcatheter arterial chemoembolization (TACE) as initial therapy. Purpose To retrospectively compare the usefulness of CLIP and JIS in predicting and stratifying the prognosis of HCC patients treated by TACE. Material and Methods Between 1995 and 2005, consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The ALBI accurately evaluated the liver function reserve of both Eastern and Western HCC patients across each BCLC stage, including those who received TACE 21 . The CLIP score, mostly applied in prognosis prediction rather than to aid in decision-making, has been externally validated in clinical practice 22 . One of our previous studies found that the CLIP system performed best among seven staging systems in predicting prognosis of patients diagnosed with HBV-related HCC 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The ALBI accurately evaluated the liver function reserve of both Eastern and Western HCC patients across each BCLC stage, including those who received TACE 21 . The CLIP score, mostly applied in prognosis prediction rather than to aid in decision-making, has been externally validated in clinical practice 22 . One of our previous studies found that the CLIP system performed best among seven staging systems in predicting prognosis of patients diagnosed with HBV-related HCC 23 .…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, TACE was performed using the Seldinger technique and in a conventional technique. [ 10 , 11 ] After performing diagnostic hepatic angiography, a 2.4 -Fr micro-catheter (Micro Ferret-18, William Cook, Bjaeverskov, Denmark) was selectively placed into the feeding arteries for selective embolization using a 0.014-inch micro-guidewire (Micromate guidewire, Terumo Clinical Supply, Gifu, Japan). After the hepatic artery was catheterized post-arteriography of the celiac and superior mesenteric vessels, TACE was performed on the hepatic artery that supplied the target tumor under super-selective catheterization using a micro-catheter; this was in accordance with blood distribution of HCC.…”
Section: Methodsmentioning
confidence: 99%